A PRODUÇÃO DE TEXTO DISSERTATIVO-ARGUMENTATIVO NO ENSINO MÉDIO: uma experiência (trans)formativa na Residência Pedagógica em Letras - Língua Portuguesa - TEIXEIRA, ANA ROXELLY BARBOSA RAMOS (2024)
Text production of different textual genres is one of the most developed skills in teaching Portuguese throughout Basic Education. The student, in this sense, needs to finish high school with sufficient linguistic skills to master the use of the most diverse textual genres that are part of everyday social life. We know, however, that many texts produced by students at this level of education still have major weaknesses in relation to what is recommended by official documents at each stage of school development. Thus, this work sought to evaluate the performance and evolution of writing of three students from the Reading and Writing Workshop developed from the Pedagogical Residency Program, with third-year students of the Integrated Technical Course in the Environment, at the Federal Institute of Paraíba (IFPB) - Cabedelo. The analysis, centered on the construction of the argumentation of the Enem essay genre, took into account the Writing Correction Manuals for Competencies III and IV and the theoretical assumptions of Textual Linguistics (KOCH, ELIAS 2016; MARCUSCHI, 2018) and approaches to Argumentation Theory. Based on the results, we qualify the execution of the Workshop as fruitful, due to the contribution it made to the quality of the students' texts, within the Enem assessment approach, and the immersion of the undergraduate in teaching practice. In effect, we argue that the competence of textual production develops in a procedural way, and the Workshop, through teaching argumentation, can improve skills in the target audience.